1994
DOI: 10.1016/0304-3959(94)90070-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief group cognitive-behavioral intervention for temporomandibular disorders

Abstract: Temporomandibular disorders (TMD) are currently viewed as an interrelated set of clinical conditions presenting with signs and symptoms in masticatory and related muscles of the head and neck, and the soft tissue and bony components of the temporomandibular joint. Epidemiologic and clinical studies of TMD confirm its status as a chronic pain problem. In this report we present results from a randomized clinical trial which compared, at 3- and 12-month follow-ups, the effects of usual TMD treatment on TMD pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 39 publications
3
83
0
2
Order By: Relevance
“…Twenty-five studies focused on specific symptoms or symptom syndromes: 5 on back pain, 3 on chronic fatigue syndrome, 3 on irritable bowel syndrome, 3 on chest pain, 2 on tinnitus, 2 on fibromyalgia and 7 on a variety of other symptoms [14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38]. Six studies focused on general somatization: 3 on unexplained physical symptoms and 3 on hypochondriasis [39, 40, 41, 42, 43, 44].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies focused on specific symptoms or symptom syndromes: 5 on back pain, 3 on chronic fatigue syndrome, 3 on irritable bowel syndrome, 3 on chest pain, 2 on tinnitus, 2 on fibromyalgia and 7 on a variety of other symptoms [14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38]. Six studies focused on general somatization: 3 on unexplained physical symptoms and 3 on hypochondriasis [39, 40, 41, 42, 43, 44].…”
Section: Resultsmentioning
confidence: 99%
“…Zusätzlich wurde nach Khan et al [156] Osamu Komiyama et al (Chiba, Japan) [166] included 60 patients with myofascial pain and limited jaw opening in a 1-year trial [74]. The study participants were randomized into one of three groups: Patients in group 1 received cognitive behavioral therapy every month according to the method of Dworkin et al [75] (patient information; training in pain-and stress-coping strategies such as progressive relaxation), group 2 received monthly cognitive behavioral therapy plus instructions in posture correction during sitting, standing, sleeping, eating, walking, and carrying heavy loads, and group 3 (controls) received every month general instructions emphasizing optimum jaw function as described by Burgess et al [25]. The trial results do suggest that posture correction in addition to cognitive behavioral therapy, as compared to cognitive behavioral interventions alone, may increase the therapeutic benefit at least in part.…”
Section: Resultsmentioning
confidence: 99%
“…This is also the conclusion of a study that used the same quality of life scale in chronic patients and obtained the lowest results in the items physical limitations and vitality 21 . However, the results are still below the expected average, confirming some studies that have used this scale and demonstrated that patients with chronic pain present low quality of life [22][23][24] . The fact that there was no increase in the scores of SF-36 in all items demonstrates that these patients can, from the moment the intervention is done, learn how to deal with everyday life in more adaptive ways.…”
Section: Discussionmentioning
confidence: 51%